Case Reports: Transformation of End-Stage Neuroendocrine Tumors With Uncontrollable Liver Metastasis Into a Novel or Additional Functional Phenotype - Kessoku, Takaomi; Kobayashi, Noritoshi; Yoneda, Masato; Kasai, Yuki; Ozaki, Anna; Okubo, Naoki; Iwaki, Michihiro; Kobayashi, Takashi; Yoshihara, Tsutomu; Kurita, Yusuke; Honda, Yasushi; Tokuhisa, Motohiko; et al. (Frontiers in Oncology, 2020)
Background: Neuroendocrine tumors (NETs) are rare, but their worldwide incidence is gradually increasing. NETs are generally heterogeneous; however, in rare cases, they have been shown to change their phenotype (i.e., non-functional to functional or one functional phenotype to another functional phenotype). Here, we present two cases of liver metastatic NETs with phenotype transformation at the advanced stage that led to life-threatening events. Case presentation: A 73-year-old woman had a small intestinal non-functional NET with liver metastasis. After uncontrollable liver metastasis at the advanced stage, she developed duodenal perforation with hypergastremia. The patient was treated with octreotide and proton pump inhibitors and underwent endoscopic closure for duodenal perforation, but her general condition gradually deteriorated, and she died 2 weeks after duodenal perforation. Another patient, a 50-year-old man, had a functional NET (gastrinoma) with liver metastasis and duodenal ulcer. After uncontrollable liver metastasis at the advanced stage, he developed hypoglycemia. Although octoreotide and diazoxide were administrated for hyperalimentation, his hypoglycemia was uncontrollable, and he died after 4 months owing to general deterioration. Conclusion: The present cases show that advanced NETs with treatment-uncontrollable liver metastasis can transform their phenotype, specifically a non-functional NET into a functional NET and one functional NET into another functional NET. These experiences suggest that the presence of treatment-resistant liver metastasis might be a hallmark of the potential to gain novel functions.